Purity and vitality of grass, clover, and alfalfa seeds - Colliver, Andrew D. (My University, 1905)
Introduction: The cheapest and most satisfactory seed of grasses, clover, or alfalfa, is an absolutely pure clean and vital seed. This is the ideal condition, and the planter whose seed is lacking in any of these qualities will be the proportionate loser. The importance of seed tests are very apparent and cannot be profitably overlooked. This is especially true of grass seeds, for the reason that adulterants, weed seed, immature and spoiled seed, is much more difficult to recognize in grasses than in cereals. The seeds used in the following tests were secured from seed houses that are patronized by Kansas farmers and one object of the experiment was to get some idea of the seeds that are being planted in Kansas at the present time. The seeds were all, as nearly as was possible to secure them, fair samples of what was being sold to the farmers. The seeds were examined and tested with regard to purity, vitality, and possibility of cleaning. In the purity tests a sample of about three hundred seeds, was counted, the weed seed separated, counted, and the predominating seed recognized. The per cent of weed -seeds given is a per cent of the total number of seeds. The foreign matter includes weed seeds, broken seeds, stems, chaff, adulterants, etc., and the per cent is calculated from the weight of the sample. The apparatus for testing vitality was a plate partially filled with sand, over which was placed a cloth, on which one variety of seeds was placed, and another cloth on top of this, with another variety of seeds, etc. From six to seven of these layers could be placed on one plate, the cloth and sand being well dampened and a second plate inverted over them. No artificial heat was necessary, the temperature varying from 65° to 90° F. At the end of one week all seeds germinated were counted and the per cent given is of the total number of seeds placed in the germinator.
Citation: Colliver, Andrew D. Purity and vitality of grass, clover, and alfalfa seeds. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Alsike Clover; Pig Weed; Lamb Quarter; Theses